Assesing the Sustainability of the Self-Declare Halal Certification Program for MSMEs in Lampung Province - Isabella, Astrid Aprica; Loliyani, Rini (Yayasan Sinergi Kawula Muda, 2026)
This study examines the sustainability and effectiveness of the Halal Self-Declare Certification Program (Business Actor Statement) for Micro, Small, and Medium Enterprises (MSMEs) in Lampung Province. The program aims to accelerate halal certification and improve MSME compliance with Halal Product Assurance (JPH) regulations. A mixed-methods approach was employed, combining surveys of certified MSMEs, in-depth interviews with Halal Product Process (PPH) facilitators, and regulatory document analysis. Sustainability was assessed across economic, social, and institutional dimensions. The findings indicate that while the program has significantly increased the number of halal-certified MSMEs, sustainability challenges persist, particularly in the consistent implementation of internal halal assurance systems, the capacity and quality of facilitation, and MSMEs’ understanding of critical halal requirements. To ensure long-term sustainability, the program requires strengthened capacity building for PPH facilitators and improved post-certification monitoring through simplified and digitalized systems. The novelty of this study lies in proposing an optimization model for the sustainability of the Sehati Self-Declare Program that integrates halal regulatory frameworks, MSME capacity, and institutional roles within the specific regional context of Lampung Province, offering a more comprehensive and practical approach than previous normative or partial evaluations.